Clinical profile of early- and late-onset colorectal cancer patients in a referral medical center in Medellín, Colombia: A comparative analysis (2024)
ABSTRACT: Introduction. Incidence of early-onset colorectal cancer (EOCRC), defined as colorectal cancer (CRC) in individuals aged < 50 years, is rising worldwide. Despite the increasing international scientific production on EOCRC, research is limited in Colombia. The objective of this study was to characterize the clinical features of adults with EOCRC and late-onset CRC (LOCRC, CRC in individuals aged ≥ 50 years). Methods. An observational, retrospective, cross-sectional study was conducted with CRC patients ≥ 18 years old at one medical center in Medellín, Colombia. Clinical and pathological data were retrieved from the Institutional Cancer Registry. Two analysis groups were established: EOCRC and LOCRC. The Chi2 test was applied to compare the variables of interest between both groups. Results. The sample included 1,202 patients, 53.5% were female (N=643) and the median age was 65 years (interquartile range: 55-73). EOCRC represented 15.9% (N=192). LOCRC tended to have more history of cardiometabolic diseases and smoking than EOCRC (p<0.001). CRC family history was proportionally more frequent in EOCRC than in LOCRC (7.3% vs 3.8%; p=0.028). Right colon tumors were more common in LOCRC (30.4% vs 21.9%; p=0.041) and left colon tumors in EOCRC (30.7% vs 23.2%; p=0.041). Only one patient had inflammatory bowel disease history. Conclusion. EOCRC is clinically distinct from LOCRC regarding pathological and toxicological history as well as tumor location. Our findings provide valuable insights for enhancing clinical decision-making, particularly in relation to age at onset in Colombian CRC patients.